Remote Work, Intrinsic Motivation, and Job Satisfaction: Unveiling the Nexus in Contemporary Organizations: Kerja Jarak Jauh, Motivasi Intrinsik, dan Kepuasan Kerja: Mengungkap Hubungannya dalam Organisasi Kontemporer - Marchelinda, Niken; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study investigates the intricate relationship between remote work arrangements, non-physical work environments, intrinsic motivation, and job satisfaction, with a focus on CV Berca Putra Delta. Data from 66 respondents were collected through questionnaires, augmented by secondary data such as company profiles and organizational structure. Employing PLS software version 3.0, the study evaluates convergent validity, discriminant validity, reliability, and R-square values. Hypothesis testing incorporates Path Coefficient and Indirect Effect analyses. The findings shed light on the multifaceted dynamics of contemporary work settings, offering valuable insights for global scholars and organizations seeking to optimize employee satisfaction in an evolving professional landscape. Highlights: The study explores the impact of remote work on job satisfaction. Intrinsic motivation is analyzed as a key driver of employee well-being. Quantitative research methods are employed to assess these relationships. Keywords: Remote Work, Intrinsic Motivation, Job Satisfaction, Non-Physical Work Environment, Quantitative Research